Potential of Flavonoids from Cat's Whiskers Plant (Orthosiphon Stamineus) as Antidiabetic Candidates through Inhibition of Tyrosine Phosphatase 1B and Aldose Reductase Proteins - Adi Budi Ramadhan, Adi Budi Ramadhan; Galih Hamdani Riansyah; Saeful Amin (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by impaired regulation of blood glucose levels. The enzymes Protein Tyrosine Phosphatase 1B (PTP1B) and Aldose Reductase are known to play significant roles in the development of insulin resistance and diabetes-related complications. This study aims to evaluate the potential of flavonoid compounds from Orthosiphon stamineus as dual inhibitors of these enzymes through an in silico approach. The research involved phytochemical screening of flavonoids reported in O. stamineus, followed by molecular docking and validation using PyRx software on the crystal structures of PTP1B (PDB ID: 1AAX) and Aldose Reductase (PDB ID: 1AH3). Docking validation was performed via redocking of native ligands, yielding RMSD values < 2 Å. Ligand-protein interactions were analyzed using Discovery Studio, while pharmacokinetic and toxicity predictions were carried out using SwissADME, pkCSM, and ProTox-II. Docking results revealed that sinensetin and salvigenin exhibited the highest binding affinities to PTP1B and Aldose Reductase, with binding energies of -9.4 and -8.4 kcal/mol, respectively. These compounds formed strong interactions with key residues at the active sites of the enzymes, indicating their potential as effective inhibitors. Pharmacokinetic evaluation showed that most compounds complied with Lipinski’s rule of five and demonstrated favorable ADME profiles, including good absorption and potential blood-brain barrier penetration. Toxicity analysis indicated that the candidate compounds were non-toxic (toxicity class III–IV) and safe for oral administration. Flavonoid compounds from O. stamineus, particularly sinensetin and salvigenin, demonstrated strong potential as dual inhibitors of PTP1B and Aldose Reductase. This study supports further development of O. stamineus flavonoids as natural multitarget therapeutic agents for the management of diabetes mellitus.